Profiles of needs satisfaction and thwarting in older people living at home: Relationships with well‐being and ill‐being indicators. Issue 3 (15th November 2017) - Vanhove‐Meriaux, Charlotte; Martinent, Guillaume; Ferrand, Claude
Abstract : Aim: To examine the profiles of basic psychological needs satisfaction (BPNS) and thwarting (BPNT) in older people living at home, their relationship with well‐being and ill‐being indicators, and how BPNS and BPNT needs were related to these indicators using regression analyses. Methods: Participants ( n = 182; mean age 73.33 years; SD 7.07 years) completed the measures of BPNS, BPNT, purpose in life, personal growth, subjective vitality, self‐esteem, positive and negative affective states, and depressive feelings. Sociodemographic data were collected. Results: Cluster analyses show two distinct profiles: (i) high degrees of BPNS and low degrees of BPNT; and (ii) moderate degrees of both BPNS and BPNT. No effect of cluster membership on demographic characteristics was reported. Multivariate analysis of variance (manova ) results showed that participants in profile 1 had a higher level of well‐being (personal growth, purpose in life, subjective vitality, self‐esteem and positive affective states) and a lower level of ill‐being (negative affective state and depressive feelings) than those in profile 2. For all participants, the findings showed that competence and relatedness need satisfactions were significantly and positively related to well‐being indicators (positive affective states, purpose of life and subjective vitality respectively). Autonomy and competence need thwarting were significantly and positively related to negative affective states. Conclusions: The present results suggest using the BPNS and BPNT scales simultaneously to better understand the mechanisms that contribute to well‐being and ill‐being in older people.Geriatr Gerontol Int 2018; 18: 470–478 .